2019
DOI: 10.1001/jamapsychiatry.2018.4530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Augmenting Standard Care for Military Personnel With Brief Caring Text Messages for Suicide Prevention

Abstract: IMPORTANCE Accessible and cost-effective interventions for suicidality are needed to address high rates of suicidal behavior among military service members. Caring Contacts are brief periodic messages that express unconditional care and concern and have been previously shown to prevent suicide deaths, attempts, ideation, and hospitalizations. OBJECTIVE To test the effectiveness of augmenting standard military health care with Caring Contacts delivered via text message to reduce suicidal thoughts and behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
140
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(148 citation statements)
references
References 37 publications
(72 reference statements)
3
140
0
1
Order By: Relevance
“…This study utilized baseline data collected before randomization from a larger treatment effectiveness trial, known as the Military Continuity Project (MCP; Comtois et al, 2019) with the following inclusion criteria: (a) Active duty, Reserve, National Guard, (b) 18 or more years of age, (c) English speaking, (d) identification to a behavioral health or medical service (inpatient, outpatient, or emergency) due to suicidal behavior-either suicidal ideation or a suicide attempt, (e) has current suicidal ideation as defined by a score of 1 or more on the Scale for Suicide Ideation, and (f) mobile phone or pager that can affordably receive 11 text messages in a year. Exclusion criteria were (a) too cognitively impaired at best mental status to consent, (b) treating clinician evaluates the intervention as contraindicated (for instance, paranoia may be exacerbated by being contacted), (c) prisoner or otherwise under judicial order such that study participation could not be considered to be truly voluntary, or (d) doesn't speak and read English well enough to consent and to understand texts in English.…”
Section: Participantsmentioning
confidence: 99%
“…This study utilized baseline data collected before randomization from a larger treatment effectiveness trial, known as the Military Continuity Project (MCP; Comtois et al, 2019) with the following inclusion criteria: (a) Active duty, Reserve, National Guard, (b) 18 or more years of age, (c) English speaking, (d) identification to a behavioral health or medical service (inpatient, outpatient, or emergency) due to suicidal behavior-either suicidal ideation or a suicide attempt, (e) has current suicidal ideation as defined by a score of 1 or more on the Scale for Suicide Ideation, and (f) mobile phone or pager that can affordably receive 11 text messages in a year. Exclusion criteria were (a) too cognitively impaired at best mental status to consent, (b) treating clinician evaluates the intervention as contraindicated (for instance, paranoia may be exacerbated by being contacted), (c) prisoner or otherwise under judicial order such that study participation could not be considered to be truly voluntary, or (d) doesn't speak and read English well enough to consent and to understand texts in English.…”
Section: Participantsmentioning
confidence: 99%
“…This study describes the results from the first RCT of an e‐mail version of the CL intervention. Prior research on caring messages has reported promising, but mixed results with a variety of outcomes (Comtois et al., ; Luxton, June et al., ). One trial conducted in the United States in the 1970s with postal mail reported reduced suicide rates compared to a group that did not receive letters, but only for the first two years of the intervention (Motto, ; Motto & Bostrom, ).…”
Section: Discussionmentioning
confidence: 99%
“…While there are several RCTs that support the efficacy of caring contact interventions in reducing rates of a variety of suicide behaviors (Carter, Clover, Whyte, Dawson, & D'Este, , ; Hassanian‐Moghaddam, Sarjami, Kolahi, & Carter, ), several trials have reported null results (Cedereke, Monti, & Ojenhagen, ; Comtois et al., ; Larkin & Beautrais, ). For example, Comtois et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this likely presence of HTE, it is important not to reject SRIB‐focused interventions prematurely based on their generally weak aggregate effects. For example, if HTE existed in the “caring text” RCT recently reported by Comtois et al (), then the relatively modest aggregate effects dismissed in an editorial of that study as predominantly null (Hoge, ) might have masked a (perhaps substantially) stronger effect in the (possibly small) subset of patients helped by the intervention, which might make that intervention a valuable component in a multimodal SRIB prevention strategy. However, it is unknown whether HTE existed because the trial was not designed to study this possibility (either in terms of targeted sampling or comprehensive assessment of hypothesized baseline modifiers).…”
Section: Discussionmentioning
confidence: 99%